EST Based Studies For Identification Of Curcumin Synthase Gene In Curcuma caesia Roxb. - Behar, Neha; Tiwari, K.L; Jadhav, SK (International Journal of Computer Sciences and Engineering, 2025)
Curcuma caesia Roxb. (Kali Haldi) is commonly used as folklore medicine in Chhattisgarh state. Curcuma species contains curcumin, which is responsible for its pharmacological activities. This compound is subject of interest due to its potential use in prevention and treatment of cancer, HIV Infection and Alzheimer's disease. This plant-specific research has always been hampered due to limited resources but with the development of turmeric EST database by David Gang's group, the molecular and functional analysis is now possible in different curcuma species. In this study, the EST regions of the major gene CURS (Curcumin synthase) from previously reported expressed sequence tag sequences (NCBI accession numbers DY384950 and DY386934) in C. longa were used, for studies in C. caesia, the amplicon generated of CURS EST sequence in C. caesia (DY384950) was sequenced using cycle sequencer. The sequence was then analysed for similarity by using BLASTn in NCBI. The expressed sequence showed 98% similarity with the CURS1 of C. longa. Identification of candidate genes using functional genomics and bioinformatics tools can significantly contribute to understanding the biosynthesis of curcumin in Curcuma caesia